EFFECTS OF FUTSAL TRAINING ON PHYSICAL FITNESS OF CHILDREN OF CAJAZEIRINHAS - PB (Fiep Bulletin - online, 2019)
The indicators point out that the results of your life are updated when you start in childhood, which means that there isa movement towards your adulthood. and quality of life. Given this, it is believed that the adoption of lifestyles in children is a veryuseful measure for the promotion of health and that benefits its motor development throughout life. The present work is to evaluate the effects of futsal in the Physical Fitness of Children of Cajazeirinhas - PB. Participate in the research 28 (twenty eight)children regularly enrolled in the Escolinha Guerreirinhos de Cajazeirinhas - PB. The evaluation instrument used was theproposal of PROESP-BR (Projeto Esporte Brasil). The children were assessed before and after the training intervention for 8weeks 2 Daily. They were submitted to a series of tests to perform an evaluation of the components related to motor performanceand to a health examination as the health indicators of PROESP-BR (Projeto Esporte Brasil). The final results are significant in allphysical performance indicators. It is concluded that futsal training in children is capable of improving the performance of cardiorespiratory endurance, localized muscle strength, upper and lower limb strength, speed and flexibility.
Keywords: Motor skills. Motor development. Futsal